Klasifikasi Frase Nama-Nama Menu Makanan Berbahasa Inggris di Koran Minggu Ini - Wiwiek Sundari (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
The language structure comprehension is closely related to the branch of linguistics that is syntax. This research studies the classification of the English food menu names taken from weekly newspaper Cempaka. The objective of this research is to describe the classification of English food menu names. Theory used in this research is based on Hockett and Brown & Miller’s. The result of this qualitative research shows that the classification of English food menu names are two classes, Noun Phrases and Possesive Phrases.